Pejabat Daerah dan Tanah Bera / Nur Nadhirah Nasaruddin - Nasaruddin, Nur Nadhirah (Faculty of Business and Management, 2025)
This report provides a comprehensive overview of my six-month industrial training experience at ‘Pejabat Daerah dan Tanah Bera’, where I worked as a practical student in the field of land management and public administration. During that period, I had the opportunity to be involved in various aspects of district and land management, including the handling of government files, the coordination of land ownership applications, as well as the exploration of the Pahang Land Geospatial System (PLGS) for land mapping purposes. ‘Pejabat Daerah dan Tanah Bera’, located in Bandar Bera, Pahang, is a leading institution committed to land management and community development, with a primary focus on providing efficient and effective services to the community. This report also covers in depth the profile, mission, and vision of the office, emphasizing the strength in land management, expertise in dealing with land issues, as well as the authority in enforcing land regulations. Additionally, a SWOT analysis is provided to assess the strengths, weaknesses, opportunities, and threats of office operations, providing valuable insight into room for improvement. Some suggestions were also put forward to streamline administrative processes and introduce digital solutions to increase efficiency and transparency in office management. Finally, this report also reflects on my industrial training experience, including the skills I have learned in the areas of administration, teamwork, and communication. All this has strengthened my understanding of the importance of effective public administration practices. This experience has also deepened my awareness of the importance of integrating technology in land management and the need for sustainable development practices that prioritize community well-being.